Universal prethermal dynamics of Bose gases quenched to unitarity - Eigen, C; Glidden, JAP; Lopes, R; Cornell, EA; Smith, RP; Hadzibabic, Z (Springer Nature, 2018)
Understanding strongly correlated phases of matter, such as the quark–gluon plasma and neutron stars, and in particular the dynamics of such systems, for example, following a Hamiltonian quench (a sudden change in some Hamiltonian parameter, such as the strength of interparticle interactions) is a fundamental challenge in modern physics. Ultracold atomic gases are excellent quantum simulators for these problems, owing to their tunable interparticle interactions and experimentally resolvable intrinsic timescales. In particular, they provide access to the unitary regime, in which the interactions are as strong as allowed by quantum mechanics. This regime has been extensively studied in Fermi gases1,2. The less-explored unitary Bose gases3,4,5,6,7,8,9,10,11 offer possibilities12 such as universal physics controlled solely by the gas density13,14 and new forms of superfluidity15,16,17. Here, through momentum- and time-resolved studies, we explore degenerate and thermal homogeneous Bose gases quenched to unitarity. In degenerate samples, we observe universal post-quench dynamics in agreement with the emergence of a prethermal state18,19,20,21,22,23,24 with a universal non-zero condensed fraction22,24. In thermal gases, the dynamic and thermodynamic properties generally depend on the gas density and the temperature, but we find that they can still be expressed in terms of universal dimensionless functions. Surprisingly, we find that the total quench-induced correlation energy is independent of the gas temperature. These measurements provide quantitative benchmarks and challenges for the theory of unitary Bose gases.